Evaluating the Effectiveness of IPSAS 23 Regulations on the Redemption of Tax Revenues by the Ekiti State Government - Niyi Awotomilusi; Oluwayomi Oso; Oluyinka OLUWAGBADE; Muyiwa Dagunduro (Journal of Accounting and Finance Management, 2023)
Abstract: The study intends to shed light on how adherence to international public sector accounting standards (IPSAS) 23 can enhance the efficient utilization of tax revenues in Ekiti State. In this study, a survey design was employed. Questionnaires were distributed directly to the specified participants, who were the Revenue Officers of Ekiti State Internal Revenue Service (EKSIRS). The entire population comprised 428 revenue officers, and we chose to use a census sampling method, which encompasses the entire population at 100%. Out of all the questionnaires distributed, 311 were returned with completed responses. The collected data was subsequently analyzed using both descriptive and inferential statistical techniques. The results analysis found that the collective impact of IPSAS 23 regulations, including revenue recognition, revenue presentation and disclosure, and revenue measurement, is a reliable predictor of tax revenue redemption by the Ekiti State Government. In essence, the implementation of these IPSAS 23 regulations significantly contributes to the redemption of tax revenues, signifying their importance in enhancing financial transparency and efficiency within the government's fiscal operations. It was concluded that revenue recognition emerges as a prominent contributor to tax revenue redemption, emphasizing the importance of accurate revenue recognition. This study then recommends that the Ekiti State Government should prioritize enhancing revenue recognition practices. This can be achieved through training and capacity-building for relevant staff to ensure accurate and timely recognition of revenue.